Mediation in proceedings involving the public finance sector entities (in the light of Art. 54a of the Public Finance Act) - Haczkowska, Monika (The Opole Studies in Administration and Law, 2020)
The amendment to the Public Finance Act (adding Article 54a) and to the Act on the responsibility for a breach of public finance discipline of 2017, introduced the possibility of concluding a settlement regarding the disputed civil law liabilities by entities of the public finance sector. Execution of a lawful settlement will not constitute a violation of public finance discipline. Until the amendment came into force, the pursuit of claims by the public finance sector entities was possible only in court. Currently it is also possible in mediation proceedings.